Electrochemical Detection of Oligopeptides at Silicon-Fabricated Micro-Liquid|Liquid Interfaces - Scanlon, M.; Herzog, G.; Arrigan, Damien (American Chemical Society, 2008)
The detection of peptides is an important bioanalytical challenge, as they are a generic class of potent molecules of biomedical and biopharmaceutical significance. In this work, the electrochemistry of seven oligopeptides at microscaled interfaces between two immiscible electrolyte solutions (µITIES) was investigated. Their transfer across the polarized interface was assisted by dibenzo-18- crown-6 (DB18C6). The ion transfer potentials of these oligopeptides were dependent on their hydrophobicitiesand their interaction with DB18C6. Micropore arrays, which were fabricated in silicon by a combination of wet and dry etch techniques, were used to enhance mass transfer and thus analytical sensitivities. The use of a gellified organic phase allowed the implementation of voltammetric stripping techniques at the liquid-organogel interface. The combination of interface miniaturization and stripping voltammetry provided limits of detection at submicromolar concentration levels. The sensitivities (calibration graph slopes) were -3205 nA µM-1 cm-2 for Phe-Phe, -1791 nA µM-1 cm-2 for Leu-Leu, -6014 nA µM-1 cm-2 for Lys-Lys, and -9611 nA µM-1 cm-2 for Lys-Lys-Lys. Mixtures of peptides were also investigated with this technique, illustrating the possibility to detect certain mixture combinations. Diverse strategies are used for the determinations.